Quality of life of young adults after a growth hormone therapy with childhood onset - Quitmann, J. H.; Rohenkohl, A. C.; Kammerer, U.; Schöfl, Christof; Bullinger, M.; Dörr, Helmuth-Günther (Deutsche Medizinische Wochenschrift, 2014)
Little is known about the health-related quality of life of young adults with childhood onset idiopathic growth hormone deficiency or neurosecretory dysfunction of growth hormone secretion, who have been treated with recombinant human growth hormone (GH).Patients were diagnosed and treated with human growth hormone at the University Children´s Hospital in Erlangen (n=85). The data of both groups were merged for analysis, because no difference between idiopathic growth hormone deficiency and neurosecretory dysfunction of growth hormone secretion in auxological. Data were found. Health-related quality of life was cross- sectionally assessed after the end of growth hormone therapy with the Short Form-36 Health Survey and the Nottingham Health Profiles for which population based norm data are available.At the time of the survey, the patients (53 m, 32 f) were 23.5 ± 4.6 years old. At start of GH therapy, age was 10.5 ± 2.8 and at the end 16.3 ± 1,4 years. At start, height SDS was -3.20 ± 1.06. GH dose was 0,026 ± 0,012 mg/kg/d (daily s. c.-injections). The increase in height SDS after the end of GH therapy was 1.69 ± 1.22. Compared to the reference population, patients reported significantly lower scores on the scales energy level, vitality, social functioning, indicating a greater social isolation, a stronger emotional reaction, an increased loss of mobility and a worse psychological state.Young adults report specific impairments after completion of GH therapy.
EVALuna2:1888